MDE in the Wild: An Exploratory Analysis on What Developers Are Discussing from Q&A Platforms - Medeiros, Carlos Alberto; Bandeira, Alan; Maia, Paulo Henrique M.; Paixão, Matheus (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Model-Driven Engineering (MDE) is an approach that considers models as first-class entities used in the software analysis, design and implementation. Although MDE has become popular in both academia and industry as an alternative for tackling the growing complexity of modern software, MDE has not been largely adopted in the software development process. A possible way to mitigate those problems consists of understanding how MDE has been applied in practice and what are the main barriers found by developers. Hence, this paper presents an exploratory study to analyse the discussions about MDE from two Q&A platforms: Stack Overflow and Software Engineering Stack Exchange. One hundred fourteen discussions have been analysed under four perspectives: discussion type, application domain, tools, and developer interest. As a result, we identified that 69, 30% of the discussions regard technical aspects, from which metamodelling is the most discussed topic, and Xtext is the most discussed tool. In addition, we observed that discussions in which developers suggest MDE-related tools tend to attract more views and answers.